Identification and analysis of heat shock transcription factor gene in Zizania latifolia - CAI Licong; TANG Mingjia; XU Jin; QI Zhenyu; FAN Feijun; ZHOU Yanhong (浙江大学学报. 农业与生命科学版)
To explore the function and potential applications of heat shock transcription factor (HSF) gene family on heat tolerance of Zizania latifolia of ‘Longjiao No. 2’, twenty-eight HSF proteins were identified and analyzed by bioinformatics methods. The physicochemical analysis showed that the theoretical isoelectric point was 4.77 to 11.63, and the molecular weight was 16.77-101.29 kDa, and the protein length was 239-661 amino acids, and the instability indexes of the whole family were more than 40. The multiple sequence alignment revealed that the DNA-binding domain of HSF protein was highly conserved with a length of about 100 amino acids. The phylogenetic tree of HSF proteins of Z. latifolia, Arabidopsis thaliana, Phyllostachys edulis, and Oryza sativa L. was constructed by MEGA 7.0 and the HSF proteins could be divided into A, B, and C classes. In the HSF family of Z. latifolia, there were 17 members in class A, seven in class B, and four in class C. The expression profiles of HSF genes under the heat stress was analyzed by real-time fluorescent quantitative polymerase chain reaction (qRT-PCR), and the physiological indexes under the heat stress were also measured. The results showed that 14 HSF genes were at high expression levels (the expression levels were increased by more than 10 times) after the heat stress (42 ℃, 12 h). Among them, the expression levels of ZlHSF-04, ZlHSF-12, and ZlHSF-27 were up-regulated most obviously, which increased by 37, 36, and 44 times when compared with the normal temperature treatment (CK), respectively. Moreover, under the heat stress, the leaves became dry and curled with a large area of water loss and chlorosis, and the maximum photochemical efficiency (Fv /Fm) of photosystem Ⅱ was significantly reduced by 49.9% compared with the CK. Besides, the relative electrical leakage (REL), and the contents of malondialdehyde (MDA), proline (Pro), hydrogen peroxide (H2O2) increased significantly by 409%, 97%, 396%, and 99%, respectively. These results lay theoretical foundations for further study of the functions of the HSF gene family under heat stress of Z. latifolia.